Intratumoral transforming boron nanosensitizers for amplifiedboron neutron capture therapy - Li, Liping (2025)
Boron neutron capture therapy (BNCT) is an advanced binary tumor-cell-selected heavy-particle radiotherapy used for treating invasive malignant tumors. However, its clinical applications have been impeded by the rapid metabolism and insufficient tumor-specific accumulation of boron agents. To tackle this issue, we develop a smart boron nanosensitizer (BATBN) capable of transforming its size in response to cancer biomarker for optimal balance between penetration and retention of boron-10 for BNCT. BATBN comprises an ultrasmall boron quantum dots (BQD) core (4 nm) conjugated with cell-penetrating peptides, which facilitates its cellular uptake and deep tumor penetration. In the tumor microenvironment, the tumor biomarker can specifically initiate a self-condensation reaction of BATBN, leading to the formation of larger-sized nanoaggregates. Due to such a specific intratumoral transformation, BATBN demonstrates a 2.4-fold increase in intratumoral boron concentration and a 5.0-fold increase in tumor retention time compared to the BQDs. Thus, the tumor volume of the BATBNs-treatment group is 2.7-fold smaller than that of BQDs in preclinical tumor models after 21 days of neutron irradiation treatment. This study presents a supramolecular strategy to endow BNCT agents with the biomarker-activated size interconversion, permitting precise and efficient BNCT for cancer treatment.